Exploring the imperative for purchasing strategic alignment to drive purchasing maturity - Nonhoff, Britta; Skipworth, Heather; Bourlakis, Michael; Mena Madrazo, Carlos; Bernon, Michael; Reefke, Hendrik (Cranfield University, 2017)
This study challenges purchasing literature on its lacking consideration of contextual factors, resulting in generic recommendations that oversimplify reality. Through a systematic review across purchasing maturity, purchasing strategic alignment and strategic purchasing literature, core conceptualisations are examined to understand underlying premises and the impact on performance links. This analysis highlights issues and unarticulated assumptions that limit the generalisability of any relationships with performance. The paper proposes a framework for future research that conceptualises alignment as a smaller gap between the current and target category maturity profile.
Keywords: Procurement; Strategic alignment; Purchasing maturity